1995
DOI: 10.1128/aem.61.3.966-971.1995
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity of Xanthomonas oryzae pv. oryzae in Asia

Abstract: Restriction fragment length polymorphism and virulence analyses were used to evaluate the population structure of Xanthomonas oryzae pv. oryzae, the rice bacterial blight pathogen, from several rice-growing countries in Asia. Two DNA sequences from X. oryzae pv. oryzae, IS1112, an insertion sequence, and avrXa10, a member of a family of avirulence genes, were used as probes to analyze the genomes of 308 strains of X. oryzae pv. oryzae collected from China, India, Indonesia, Korea, Malaysia, Nepal, and the Phil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
81
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 162 publications
(87 citation statements)
references
References 17 publications
3
81
0
Order By: Relevance
“…1). These findings agreed with some earlier reports (Adhikari et al 1995) that most of the Xoo strains from Nepal and India were virulent on cultivars possessing BB resistance gene xa5, while the isolates from Indonesia, Korea, Malaysia and Philippines were avirulent.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…1). These findings agreed with some earlier reports (Adhikari et al 1995) that most of the Xoo strains from Nepal and India were virulent on cultivars possessing BB resistance gene xa5, while the isolates from Indonesia, Korea, Malaysia and Philippines were avirulent.…”
Section: Discussionsupporting
confidence: 93%
“…However, the characterization of isolates at the molecular level may further help in delineating isolates belonging to the same race or group, studying the pathogenic diversity across the region ⁄ country and monitoring the isolates at the field level. Based on molecular typing, genetic diversity has been reported in the Xoo populations from different rice-growing countries (Leach et al 1992;Nelson et al 1994;Adhikari et al 1995;Ardales et al 1996;George et al 1997;Yashitola et al 1997;Lee et al 1999). In India, the number of reported pathotypes varied from 2 to 11 depending on the number of differential cultivars used (Gupta et al 1986;Reddy and Reddy 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Although unique information and different levels of population diversity can be revealed by the use of different primers/probes (Louws et al 1994;Nelson et al 1994), our results revealed that REP1R-Dt/REP2-D is not suitable for typing Xoo at the subspecies level. While insertion sequences and transposable elements may have strong impact on the evolution of bacterial genomes (Siguier et al 2014), data from previous studies generally indicated a partial or little relationship between molecular haplotype and pathotype (Nelson et al 1994;Adhikari et al 1995Adhikari et al , 1999Ochiai et al 2000;Li et al 2009). A similar phenomenon was observed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Xa21 is known to confer broad-spectrum resistance to multiple Xoo strains from many countries (Wang et al 1996;Tripathi et al 2014). Xa21 was resistant to almost all Xoo strains collected from Sri Lanka in 1995 (Ochiai et al 2000), from the Punjab state in northern India in 1997 (Singh et al 2003), from13 major ricegrowing provinces in China in 2003 (Li et al 2009), and from 20 different states of India during 2004-2010 (Mishra et al 2013); however its resistance was gradually defeated in northern India (Lore et al 2011), Nepal (Adhikari et al 1999) and Korea (Lee et al 1999). The expression of Xa21 is activated by Xoo infection, but its cognate PAMP, which appears to be a common molecule in Xoo and X. campestris pv.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation